Cripping sexualities: An analytic review of theoretical and empirical writing on the intersection of disabilities and sexualities. Issue 5 (2nd May 2017) - Santinele Martino, Alan
Abstract: This paper provides a review of some of the literature addressing the juncture of disabilities and sexualities and invites sociologists to build on this work and take part in this important intersectional field. First, I discuss the central relevance of an intersectional lens for making sense of the unique experiences of queer people with disabilities who are located at the crossroads of various stratified systems. Then, I discuss some of the many unique challenges that queer disabled people face when exploring their sexuality, establishing relationships, and remaining sexual. The invisibility, marginalization, and discrimination of queer people with disabilities in both queer and disability communities are the focus on the third section. The fourth section speaks to current theoretical dialogues between disability studies and queer theory that have illuminated new pathways for theorizing the intersection of disabilities and sexualities, "cripping" sociological theories, and reimagining disability within sociology. As I demonstrate, this literature is growing; however, myriad exciting opportunities for empirical and theoretical sociological exploration remain and I will conclude with a discussion of possible directions for future research.